2009
DOI: 10.1108/09600030910942403
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the value of supply chain management periodicals

Abstract: Purpose -The purpose of this paper is to provide rankings of quality of peer reviewed periodicals for faculty research use, rankings of usefuless of both peer reviewed and non-peer reviewed periodicals for teaching and outreach purposes, and rankings of usefulness of search engines for finding articles. Design/methodology/approach -An online survey was conducted during the Autumn Semester of 2006. 82 periodicals were identified as relevant to the Supply Chain Management field. Respondents were asked to rank th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 17 publications
1
61
0
Order By: Relevance
“…Using this approach, the authors concluded that Journal of Business Logistics, International Journal of Physical Distribution & Logistics Management, and The International Journal of Logistics Management were the top three journals. This approach yielded similar results from other non-citation-based analyses of journal quality, with the top three journals being the same in both approaches (Menachof et al, 2009;Gibson et al, 2004), thus affirming the robustness of the technique. Citation analysis has also been used in non-logistics, but SCM-related disciplines.…”
Section: Literature Reviewsupporting
confidence: 66%
“…Using this approach, the authors concluded that Journal of Business Logistics, International Journal of Physical Distribution & Logistics Management, and The International Journal of Logistics Management were the top three journals. This approach yielded similar results from other non-citation-based analyses of journal quality, with the top three journals being the same in both approaches (Menachof et al, 2009;Gibson et al, 2004), thus affirming the robustness of the technique. Citation analysis has also been used in non-logistics, but SCM-related disciplines.…”
Section: Literature Reviewsupporting
confidence: 66%
“…1 Distribution of literature reviews over the journal categories and types of reviews consultation (see Appendix). The journal selection was based on SCM journal rankings (Zsidisin et al 2007;Menachof et al 2009), which were synthesized and classified into the groups purchasing and supply chain management (11 PSCM journals), operations research, management science, production and operations management (14 OR/MS/POM journals), international marketing management (5 IMM journals), and general management and strategy (5 GMS journals) with the help of the Harzing (2012) journal quality list. The manual review of the pre-selected journals resulted in 71 initial hits (25 relevant LRs), and the database search produced 102 hits in BSP (10 new and relevant LRs) and 101 hits in ABI (4 new and relevant LRs).…”
Section: Literature Review Process Of This Tertiary Studymentioning
confidence: 99%
“…Second, as similar assessments in other fields have based their analyses on the discipline's flagship journals (Collier and Bienstock 2007) and because Werner, Praxedes, and Kim (2007) found that the journal tier is a significant predictor for the reporting of nonresponse-higher-ranked journals address nonresponse bias more often-our aim was to focus on prestigious journals in the logistics research community. Thus, we based our choice on evaluations which focus on the academic prestige, readership and impact of logistics journals (Emmelhainz and Stock 1989;Fawcett, Vellenga, and Truitt 1995;Gibson and Hanna 2003;Gibson, Hanna, and Menachof 2004;Kumar and Kwon 2004;Menachof et al 2009). Of course, journal rankings might be viewed ambiguously within the research community.…”
Section: Samplingmentioning
confidence: 99%